Technological properties of indigenous Lactococcus lactis strains isolated from Lait caillé, a spontaneous fermented milk from Burkina Faso. Issue 1 (17th February 2020) - Bayili, Geoffroy Romaric; Johansen, Pernille Greve; Hougaard, Anni Bygvrå; Diawara, Bréhima; Ouedraogo, Georges Anicet; Jespersen, Lene; Sawadogo-Lingani, Hagretou
Abstract: The experiments reported in this research paper aimed to determine the technological properties of indigenous Lactococcus lactis strains isolated from Lait caillé, a spontaneous fermented milk, from the perspective of starter culture development. Fermentations were conducted to determine the acidification patterns. The ropy character, growth in 0.04 g/ml NaCl and citrate metabolism were additionally tested. Furthermore, the rheological properties of samples from selected strains and the impact of cold storage were evaluated. Based on the rate of acidification, the indigenous strains were divided into 2 groups depending on their fermentation time, i.e. 10–13 h (fast acidifier), and up to 72 h (slow acidifier), respectively. The physiological tests suggested that most of these strains produced exopolysaccharides but none could ferment citrate. The flow properties of the samples inoculated by the fast acidifier strains showed a time-dependent shear thinning behaviour, while their viscoelastic properties corresponded structurally to those of weak gels. Cold storage decreased the viscosity and CFU counts for most of the indigenous strains tested. This study is a step towards the definition of starter cultures for African spontaneous fermented milks such as Lait caillé.